2013
DOI: 10.1007/s10142-013-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of Zea mays roots reveals roles for jasmonic acid and terpenoids in resistance against Phytophthora cinnamomi

Abstract: Phytophthora cinnamomi is a soil-borne plant pathogen that has caused widespread damage to vulnerable native ecosystems and agriculture systems across the world and shows no sign of abating. Management of the pathogen in the natural environment is difficult and the options are limited. In order to discover more about how resistant plants are able to defend themselves against this generalist pathogen, a microarray study of plant gene expression following root inoculation with P. cinnamomi was undertaken. Zea ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Transcriptome analysis of maize roots post-infection by P. cinnamomi also revealed over expression of several genes involved in the biosynthesis of JA and Et [69]. Furthermore, the expression of a copalyl diphosphate synthase (CPS), An2, was induced by R. microsporus and preceded kauralexin accumulation, which suggested that kauralexin production is dependent on An2 activity [27].…”
Section: Jasmonic Acid and Ethylene Have A Synergistic Effect In Maizementioning
confidence: 96%
See 4 more Smart Citations
“…Transcriptome analysis of maize roots post-infection by P. cinnamomi also revealed over expression of several genes involved in the biosynthesis of JA and Et [69]. Furthermore, the expression of a copalyl diphosphate synthase (CPS), An2, was induced by R. microsporus and preceded kauralexin accumulation, which suggested that kauralexin production is dependent on An2 activity [27].…”
Section: Jasmonic Acid and Ethylene Have A Synergistic Effect In Maizementioning
confidence: 96%
“…JA/Et synergy has been demonstrated in maize [27,69]. Application of a combination of these phytohormones resulted in a build-up of kauralexins and zealexins, novel diterpenoid and sesquiterpenoid phytoalexins, respectively, which far exceeded the accumulation induced by each hormone individually [27].…”
Section: Jasmonic Acid and Ethylene Have A Synergistic Effect In Maizementioning
confidence: 99%
See 3 more Smart Citations